2019
DOI: 10.3221/igf-esis.50.28
|View full text |Cite
|
Sign up to set email alerts
|

Using a Hashin Criteria to predict the Damage of composite notched plate under traction and torsion behavior

Abstract: The volume fraction effect of carbon fiber in an epoxy matrix in the vicinity of the notch on the traction and torsion behavior were studied. This volume fraction which increases with the reduction of the thickness is a parameter which proved effective on the capacity of resistance. The calculations are done with the numerical code ABAQUS 2009 [1]. using the model Hashin with shell elements of the structure. The objective of this study is to simulate the damage of stratified composite materials, the effect of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…The Hashin criteria failure indices pertain to the die and fiber failures and encompass four distinct failure modes. The transverse stress normal component receives maximum stress parameters in three-dimensional problems [27]. The Hashin Damage Criterion parameter is taken from research by Debski et al [28] shown in Table 7.…”
Section: Study Case Analysismentioning
confidence: 99%
“…The Hashin criteria failure indices pertain to the die and fiber failures and encompass four distinct failure modes. The transverse stress normal component receives maximum stress parameters in three-dimensional problems [27]. The Hashin Damage Criterion parameter is taken from research by Debski et al [28] shown in Table 7.…”
Section: Study Case Analysismentioning
confidence: 99%
“…Due to the anisotropic elasticity of GFRP, the model used engineering constants to define the tensile modulus of elasticity, shear modulus, and Poisson’s ratio in three directions. The Hashin damage criterion has been widely used in progressive damage analysis of composite materials and in defining the failure mode of GFRP strips during the damage stage [ 32 , 33 ]. The main parameters in the Hashin damage criterion were taken based on the material property test results, which are shown in Table 1 .…”
Section: Finite-element Simulation and Parametric Analysismentioning
confidence: 99%
“…Gu and Chen [38] affirmed the amenability arising from the criterion's ease of use though indicating that it does not always correlate well to experimental results. Chaht [39] using the Hashin criterion to simulate stratified composite material damage using shell elements. Li and Ju [40] found that including the shear stress term in the Hashin fibre tension failure criterion led to an underestimation of failure strength.…”
Section: Review Of Some Widely-used Failure Criteriamentioning
confidence: 99%